2023
DOI: 10.1007/s10681-023-03167-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drought tolerance in sugarcane genotypes using the membership function value of drought tolerance (MFVD)

Abstract: Drought is a worldwide problem seriously in uencingsugarcane (SaccharumL. spp. hybrids) production.The long-term domestication and selective breeding in arti cial environments may have reduced the drought resistance of sugarcane. The objective of this study was to determine drought tolerance in a 138genotype of elite sugarcane hybrids using the membership function value of drought tolerance (MFVD) based on the drought-tolerant coe cient (DC) of four yield traits (biomass, stalk weight, stalk diameterand stalk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…In the present study, MFVD was significantly and positively correlated with the DC of all yieldrelated traits in both plant cane and ratoon cane. In a previous study, positive correlations have been found between MFVD and DC of biomass, stalk weight, stalk diameter, and stalk height at the growth stage and seedling stage [30], which is also supported by our results. In the association mapping panel evaluated in this study, we observed a wide variation of DC and MFVD, suggesting that there are genetic sources of drought tolerance in the panel used in this study.…”
Section: Phenotypic Data Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, MFVD was significantly and positively correlated with the DC of all yieldrelated traits in both plant cane and ratoon cane. In a previous study, positive correlations have been found between MFVD and DC of biomass, stalk weight, stalk diameter, and stalk height at the growth stage and seedling stage [30], which is also supported by our results. In the association mapping panel evaluated in this study, we observed a wide variation of DC and MFVD, suggesting that there are genetic sources of drought tolerance in the panel used in this study.…”
Section: Phenotypic Data Analysissupporting
confidence: 92%
“…Ratooning ability was calculated from (CY of ratoon cane/CY of plant cane) × 100. The drought-tolerant coefficient (DC) of yield-related traits measured was calculated as: where DC ij was the drought-tolerant coefficient of the trait (j) for the genotype (i); X ijWS and X ijNS were the values of the trait (j) for the genotype (i) evaluated under WS and NS conditions, respectively [ 30 ]. Drought tolerance for each sugarcane cultivar was evaluated by the membership function value of drought tolerance (MFVD) using the approach of Chen et al (2012) [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More accurate sugarcane models for Brazil's sandy soils are essential to optimize water management decisions to (1) invest in irrigation in order to increase crop productivity and to (2) withhold water, especially in irrigated systems prior to harvest to maximize sugar content. Yield gaps for sugarcane can be closed by using crop breeding for droughttolerant cultivars [65] and irrigation [65,66]. If future climate changes increase sugarcane yield, payback for irrigation investments could decrease from 14 years to only 3 years, making such investments more feasible [67].…”
Section: Sustainability Implicationsmentioning
confidence: 99%